Biomass-based supercapacitors : design, fabrication and sustainability - Aziz, Md. Abdul (Research scientist); Shah, Syed Shaheen (Wiley, 2023)
BIOMASS-BASED SUPERCAPACITORS Authoritative resource addressing the fundamentals, design, manufacturing, and industrial applications of supercapacitors based on biomass Biomass-Based Supercapacitors presents a systematic overview and recent developments in the research, design, and fabrication of supercapacitors using biomass, discussing fundamentals, advancements, industrial applications, and the manufacturing process of biomass-derived supercapacitors. The text also considers environmental and economic aspects of the technology, along with biomass-based supercapacitors in the context of circular economy. Written by a team of international experts in the field of supercapacitors, Biomass-Based Supercapacitors covers sample topics such as: Basic foundational knowledge surrounding supercapacitors, electrochemical techniques for supercapacitors, and different types of supercapacitors Biomass derived electrode materials for supercapacitors, such as activated and non-activated carbon, carbon from pretreated biomass, carbonate salts-activated carbon, and more Electrolytes, separators, and packaging materials for supercapacitors using biomass and binding materials from biomass for supercapacitors Future outlooks and challenges for the development of biomass-based supercapacitors, from the lab to practical applications in industry Biomass-Based Supercapacitors is an excellent resource for academic researchers and industrial scientists working in the areas of supercapacitor fabrication, energy materials and energy storage devices, electrochemistry, materials science, biomass conversion, green chemistry, and sustainability.
Keywords: Supercapacitors.; Biomass.; elektronické knihy; electronic books